Representações sociais do trabalho voluntário em uma associação de assistência a pacientes oncológicos - Souza, Luziana Karla Braga De (2018)
This research aims to map the social representations of voluntary work among the people working at Associação do Voluntariado Vida Viva, located in Varginha/MG, considering the Social Representations Theory (SRT). Such theory, elaborated by Serge Moscovici in 1961, focus on the understanding of social reality from a historical-critical perspective, articulating it with the social construction of reality through an interpretative symbolic approach (MOSCOVICI, 2015). The work also aims to map social representations of voluntary work among the people working at Associação do Voluntariado Vida Viva by considering the economic and social importance of this type of work in contemporary society. It can be seen as a knowledge space under construction, representing one of the pillars of non-governmental organizations (CALDANA et al., 2012). The voluntary work is convergent with the adoption of the interpretative symbolic approach defended by the SRT, which is used for the understanding of the symbolic interactions between the worker and the practice. From this interaction, the social representation is born. A field research will be performed to demonstrate this symbolic universe, understanding which symbols and meanings are relevant to the voluntary work developed in the association. The research is based on semi-structured interviews, with a sample of 15 volunteers, as well as a participant observation conducted at the researched institution. The analysis of the data is performed through the technique of content analysis (BARDIN, 1977).